Dubai Clinical Practice Guidelines for Autism Spectrum Disorder (ASD) in Children and Adolescents (from Birth to 18 Years of Age) - Albanna, Ammar; Sultan, Meshal; Derby, Hanan; Arjamand, Fekrya; AlShuaibat, Suha; Alloub, Zeinab; Al Hejailan, Rasha; Kair, Hawk; Helou, Maya; Obaid, Hanan Ali; Alrustamani, Latifa; Muhsineh, Shatha; et al. (Dubai Medical Journal, 2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by impairments in social interaction and communication, along with restricted interests and repetitive behaviors. It is a lifelong condition that can profoundly impact the individual, their family, and the community. Given that the etiology of ASD is multifactorial, and the rise in ASD prevalence internationally, establishing evidencebased clinical guidelines is critical. The UAE offers a range of services for children and adolescents with ASD with the aim to improve the quality of services within a comprehensive system of care. The Dubai Clinical Practice Guidelines for Autism Spectrum Disorder (ASD) in Children and Adolescents (from Birth to 18 Years of Age), Version 1 aims to provide clinical guidance to healthcare professionals involved in managing ASD based on the best available local and international evidence. ASD management approaches are ranked in these guidelines based on their strength and availability of empirical evidence to support them. The clinical guidelines shall be read in conjunction with any new empirical evidence that arises after 2021.